Rethinking Blood Pressure Monitoring in Children and Adolescents. Issue 3 (May 2018) - Beal, Judy A.
Abstract : Most pediatric providers do not think of hypertension as a common diagnosis in children and adolescents. However as reported by the American Academy of Pediatrics (AAP) in 2017, prevalence of hypertension has increased significantly since 1988, with most cases going undiagnosed or treated. Our pediatric nursing expert, Dr. Beal, discusses the new AAP guidelines on hypertension in children and adolescents.